Metal-Assisted Hydrolysis Reactions Involving Lipids: A Review - Williams, Dominique E.; Grant, Kathryn B. (Frontiers in Chemistry, 2019)
This report covers major advances in the use of metal ions and complexes to hydrolyze ester and phosphate ester lipid bonds. These metal-based Lewis acids have been investigated as catalysts to isolate fatty acids from biological sources, as probes to study phospholipid bilayer properties, as tools to examine signal transduction pathways, and as lead compounds toward the discovery of therapeutic agents. Metal ions that accelerate phosphate ester hydrolysis under mild conditions of temperature and pH may have the potential to mimic phospholipase activity in biochemical applications.